2020
DOI: 10.1016/j.annemergmed.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Patient Discharge Instructions in the Emergency Department and Their Effects on Comprehension and Recall of Discharge Instructions: A Systematic Review and Meta-analysis

Abstract: We conduct a systematic review with meta-analysis to provide an overview of the different manners of providing discharge instructions in the emergency department (ED) and to assess their effects on comprehension and recall of the 4 domains of discharge instructions: diagnosis, treatment, follow-up, and return instructions.Methods: We performed a systematic search in the PubMed, EMBASE, Web of Science Google Scholar, and Cochrane databases for studies published before March 15, 2018. A quality assessment of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 66 publications
(123 reference statements)
2
102
0
Order By: Relevance
“…A list of behaviours must be understood, recalled and acted upon. However, patients typically cannot recall a substantial amount of relevant information, with recollections being sensitive to format (Hoek et al, 2020). Verbal communication is recalled less than written information or, better still, video.…”
Section: Hypothesis 2cmentioning
confidence: 99%
“…A list of behaviours must be understood, recalled and acted upon. However, patients typically cannot recall a substantial amount of relevant information, with recollections being sensitive to format (Hoek et al, 2020). Verbal communication is recalled less than written information or, better still, video.…”
Section: Hypothesis 2cmentioning
confidence: 99%
“…In our study, patients perceive their understanding of the treatment plan good to very well. However, many studies have shown that patients regularly do not understand their treatment plan or discharge instructions [35,36]. More importantly, most patients appear to be unaware of their lack of understanding, which might be also the case in our study and an explanation for the high scores [37,38].…”
Section: Plos Onementioning
confidence: 47%
“…Our findings support recent evidence that the addition of written discharge instructions to verbal instructions shows promise for the ED population. 4 However, the provision of printed and mobile accessible discharge instructions for pain relief advice was not associated with a difference between groups for our primary outcomes. Other studies using pain scores as primary outcomes for pain management interventions at ED discharge usually focus on comparing the efficacy of different analgesic regimes.…”
Section: Discussionmentioning
confidence: 74%
“…Verbal instructions are standard in the ED discharge process. 4 These are often incomplete and brief, averaging 76 s. 5 Written ED discharge instructions can be a handwritten or typed letter, a pre-formatted instruction sheet to be filled out or a generic pre-printed education document. 6 A recent systematic review and meta-analysis found that the addition of written to verbal instructions at ED discharge may increase patient recall from 47% to 58% on average 4 although readability levels of written discharge instructions are found to be consistently higher than the levels recommended for the general population.…”
Section: Introductionmentioning
confidence: 99%